Experimental study on the foam performance and fire extinguishing performance of aqueous foam stabilized by alkyl polyglucoside and urea. Issue 1 (1st February 2022) - Li, Fan; Yu, Xiaoyang; Zong, Ruowen
Abstract: Foam extinguishing agents are the most effective extinguishing agents for liquid fires. The search of relevant domestic and foreign commercial foam fire extinguishing agent patents found that most commercial foam fire extinguishing agent formulations contain urea. In order to understand the mechanism of urea's influence and clarify the application parameters of urea-added aqueous foam in the fire extinguishing process, this research investigated the surface tension, foaming ability, foam stability, and fire extinguishing performance for alkyl polyglucoside and alkyl polyglucoside/urea foams. It is found that the addition of urea promotes the formation of surfactant micelles, resulting in a decrease in critical micelle concentration, while the surface tension and foaming ability of the alkyl polyglucoside solution are only moderately affected by the urea. Besides, urea significantly improves the fire extinguishing performance of alkyl polyglucoside foam and the influence of urea concentration on fire extinguishing time is remarkable. On the one hand, the enhanced extinguishing performance can be explained by the increase of foam stability. On the other hand, urea produces incombustible gases such as NH3 and CO2 under the action of the high temperature of the fire, which may improve the fire extinguishing performance by cooling effect and asphyxiation effect. The increase in expansion ratio and the foam flow rate are beneficial to shorten the extinguishing time. The research results can guide the design of foam extinguishing agents.